X-ray diffraction studies of Ti0₂ powders by a sol-gel method / Amin Aadenan - Aadenan, Amin (2010)
Titanium dioxide (Ti02) powders were synthesized by the sol-gel method under room temperature using titanium (IV) methoxide as the precursor. The Ti02 powders were set to values of pH 8 and pH 6 respectively in order to observe its effect on the crystalline structure. Beside, the Ti02 powders were calcined at 800 °C for 3, 5, and 10 hours of heat treatment. The synthesized powders were characterized by X-ray diffraction (XRD). XRD patterns revealed that, the samples possessed a mixed crystalline structure where pH 8 Ti02 powder comprising of anatase and rutile, meanwhile, pH 6 Ti02 powder consisting of anatase, rutile and minor amounts of brookite crystalline structure. Upon heating, the anatase was improved to rutile as the time increased. By lowering the pH,'the transformation of anatase-rutile was consumed lower time of heat treatment. In TGA results, the stable weight loss of pH 8 and pH 6 Ti02 powders were observed in the temperature range of 700 °C to 900 °C.